Loyalitas Pegawai Ditinjau dari Kecerdasan Emosional, Komitmen, Self Efficacy, dan Kompetensi (Studi Kasus pada KPPBC TMP B Surakarta) - Yesi Yeshinta; Sri Hartono; Istiatin Istiatin (Universitas Muria Kudus, 2020)
The purpose of this study was to determine the influence emotional intelligence, commitment, self efficacy, and competence towards employee loyalty at KPPBC TMP B Surakarta. This research is a quantitative research. The study population consisted of 101 employees at KPPBC TMP B Surakarta, but only 65 samples were taken. The data was collected by using a questionnaire. In this study, the data was analyzed using the classic assumption test, multiple linear regression analysis, t test, F test, and the coefficient of determination test. The results showed the F test (simultaneous) showed emotional intelligence, commitment, self efficacy, and competency simultaneously had a significant effect on employee loyalty. The results of the t test (partial) showed emotional intelligence had a negative and significant effect on employee loyalty in KPPBC TMP B Surakarta. Meanwhile commitment, self efficacy, and competence have positive effect on employee loyalty in KPPBC TMP B Surakarta individually (partially).